Conductivity enhancement of silver nanowire networks via simple electrolyte solution treatment and solvent washing. (30th April 2018) - Gu, Jiahui; Wang, Xuelin; Chen, Hongtao; Yang, Shihua; Feng, Huanhuan; Ma, Xing; Ji, Hongjun; Wei, Jun; Li, Mingyu
Abstract: As a promising replacement material for indium tin oxide in flexible electronics, silver nanowires (AgNWs) usually need complicated post-treatment to reduce the high contact resistance across the intersections when used as transparent conductive films. In this work, a widely applicable nano-joining method for improving the overall conductivity of AgNW networks with different kinds of electrolyte solutions is presented. By treatment with an electrolyte solution with appropriate ionic strengths, the insulating surfactant layer (polyvinylpyrrolidone, PVP) on the AgNWs could be desorbed, and the AgNW network could be densified. The sheet resistance of the AgNW film on a glass slide is reduced by 60.9% (from 67.5 to 26.4 Ohm sq −1 ) with a transmittance of 92.5%. High-resolution transmission electron microscopy analysis indicates that atomic diffusion occurs at the intersection of two AgNWs. Thus, metallurgical bonding on the nanometer scale is achieved across the junctions of the AgNWs, leading to a significant enhancement in the conductivity of the AgNW network.